How Does the Young Generation in Jabodetabek Intend to Participate in the Cash Waqf-Linked Sukuk Retail? - Lubis, Deni; Savira, Salsabila (Universitas Islam Negeri Mataram, 2025)
Waqf today is much easier because of the presence of technology, especially cash waqfs. Cash waqf-linked sukuk is one of the instruments provided to make it easier for donors to donate. SWR004 purchases achieved the highest sales volume of Rp112.563 billion in 2023, compared to SWR003 of Rp38.25 billion in 2022. Online sales of retail cash waqf linked to Sukuk demonstrated favorable performance at IDR24,128, with the highest number of waqifs at 618 waqifs. However, a decline in online CWLS Retail bookings has been observed both in terms of nominal bookings and the number of waqifs. This study aims to analyze the intention of the Y and Z generations to purchase cash waqf-linked sukuk retail, utilizing the Technology Acceptance Model (TAM) approach and additional waqf literacy variables. This study employed quantitative methods with primary data and involved 200 respondents. Sampling was conducted using the nonprobability sampling method with the convenience sampling technique and analyzed with Structural Equation Model-Partial Least Squares. The results indicate that waqf literacy, perceived usefulness, and trust in BWI and waqf institutions have a significant positive effect on the intention to purchase retail CWLS. Trust variables can mediate perceived transparency and intention to purchase retail CWLS.